FGF20 Protected Against BBB Disruption After Traumatic Brain Injury by Upregulating Junction Protein Expression and Inhibiting the Inflammatory Response - Chen, Jun; Wang, Xue; Hu, Jian; Du, Jingting; Dordoe, Confidence; Zhou, Qiulin; Huang, Wenting; Guo, Ruili; Han, Fanyi; Guo, Kaiming; Ye, Shasha; Lin, Li; et al. (Frontiers in Pharmacology, 2021)
Disruption of the blood-brain barrier (BBB) and the cerebral inflammatory response occurring after traumatic brain injury (TBI) facilitate further brain damage, which leads to long-term complications of TBI. Fibroblast growth factor 20 (FGF20), a neurotrophic factor, plays important roles in brain development and neuronal homeostasis. The aim of the current study was to assess the protective effects of FGF20 on TBI via BBB maintenance. In the present study, recombinant human FGF20 (rhFGF20) reduced neurofunctional deficits, brain edema, Evans blue penetration and neuroinflammation in a TBI mouse model. In an in vitro TNF-α-induced human brain microvascular endothelial cell (HBMEC) model of BBB disruption, rhFGF20 reduced paracellular permeability and increased transendothelial electrical resistance (TEER). Both in the TBI mouse model and in vitro, rhFGF20 increased the expression of proteins composing in BBB-associated tight junctions (TJs) and adherens junctions (AJs), and decreased the inflammatory response, which protected the BBB integrity. Notably, rhFGF20 preserved BBB function by activating the AKT/GSK3β pathway and inhibited the inflammatory response by regulating the JNK/NFκB pathway. Thus, FGF20 is a potential candidate treatment for TBI that protects the BBB by upregulating junction protein expression and inhibiting the inflammatory response.